P88 LEFT ATRIAL APPENDAGE CLOSURE DEVICE COMPLICATED BY LATE ONSET PERICARDIAL EFFUSION AND TAMPONADE: A CASE REPORT. (18th May 2022) - Albani, S; Pisano, F; Berlier, N; Pelloni, E; Caterina, B; Biava, L; Contu, L; Scacciatella, P
Abstract: Background: Late onset complications of left atrial appendage occlusion (LAAO) device procedure are anecdotal and there are no such complications reported in literature using Cardia Ultraseal (Cardia, USA). Case Summary: We report the case of a 74–year–old Caucasian man affected by paroxysmal atrial fibrillation with significant bleeding risk (familiar thrombocytopenia, macroscopic hematuria episodes during therapy with direct oral anticoagulants, HAS–BLED risk score: 4) and ischemic risk as well (CHADSVASC score: 3). The patient was treated with LAAO device implantation for high bleeding risk. Subsequently, after 26 days from LAAO procedure, he was admitted to the emergency department for hematic cardiac tamponade. The patient was successfully treated with subxyphoidal pericardiocentesis in the acute phase, unfortunately cardiac arrest occurred during the transfer to the referral hospital for urgent cardiac surgery. Permanent neurological damage was reported and the patient died on day 28. Discussion: There are several clinical and radiological aspects that may suggest a cause–effect relationship with the occurrence of hematic pericardial effusion and LAA occlusion device implantation: firstly the pericardial effusion was hematic and its occurrence was preceded by acute interscapular pain suggesting an acute pericardial irritation caused by the hematic effusion and secondly, the CT scan played an "indirect key role" excluding several causes of hematic pericardial effusion (such as aortic dissection and solid tumors that could infiltrate the pericardial membrane), thirdly there are no other anamnestic events that may be associated with this clinical manifestation (such as trauma). The low flexibility of the Cardia Ultraseal (Cardia, Inc., Eagan, MN, USA) nitinol mesh structure, as previously reported in others settings, may be associated to increased torque of the device by the beating heart. A bench test showed that the Ultrasept, a large–mashed device for interatrial defect closure, very similar to Ultraseal, needs a high compression force during implantation as a result of its low radial strength. In addition, compared to other devices, the bulb part is much larger. Consequently, when the device is deeply inserted in LAA, a higher surface area within the appendage wall is directly overlapped, having more chance of causing friction.All these aspects could be responsible of wall erosion.